Essays on debt maturity - Laureano, Luis Miguel da Silva (2011)
This dissertation consists of three major empirical studies about debt maturity following two introductory chapters describing the data used and also the most relevant theoretical and empirical work in the existent literature. In the first empirical study we examine the debt maturity trend from 1980 to 2004 for US firms and identify if the changes in the debt maturity determinants over time help to explain that same trend. We find evidence of a statistically significant downtrend. Unconstrained firms have significantly higher average debt maturity than constrained ones. We model the average debt maturity using the major determinants found in the most relevant literature. The results give mixed support to most of the existing theories. Opposite to the agency costs theory, we find that firms with higher growth options have higher average debt maturity ratios. Being a regulated firm yields more long term debt and larger firms have higher debt maturity in their capital structures. The signaling hypothesis finds weak support in the results. We provide evidence that our model significantly overestimates the average debt maturity and that the changes occurred over time in the firm characteristics used in the model do not explain the overall trend observed in the debt maturity ratio. In the second empirical study we investigate the relation between debt maturity and macroeconomic conditions for US industrial firms from 1974 to 2004. We find some evidence that firms hold more short-term debt during economic recessions. However, the results obtained in the financially constrained and unconstrained subsamples are statistically weakly significant. At the firm specific level we find no support for the agency costs hypothesis. In contrast, our results show a positive relation between long-term debt and growth options with a stronger economic impact in unconstrained firms. We find a statistically significant positive relation between size and debt maturity and no evidence that being a regulated firm has any influence on debt maturity choice. We also find no evidence that supports the signaling mechanism in which firms use their debt maturity choice to signal their quality to the market. The matching principle receives good support in our study, particularly from constrained firms. We find that firms with higher effective tax rates borrow more long-term.The third empirical study focuses on using different approaches to provide support to previous results and to find additional evidence in explaining the choice of the debt maturity level. Through logistic regression we find that larger firms with more growing opportunities and asset maturity and that are subject to higher tax rates are more likely to have higher average debt maturity in their capital structure. Using cluster analysis we are able to clearly identify two distinct groups. We examine the debt maturity in each group and find good support to the previous findings. Using classification trees we find similar results to those obtained using logistic regression while using regression trees yields the indication that the largest firms and those with highest asset maturity are expected to have, on average, the highest debt maturity ratios.